“WAS IT HIS MILK”? A CASE REPORT OF CHLORPYRIFOS AND CYPERMETHRIN MIXED POISONING IN A TODDLER. - Ebiju, Isaac; INNOCENT, AYESIGA; Wekha , Godfrey; Mugambe, Julius Bruno; Nabaweera, Rebbecca; Musiime, Elias; Magala, Primrose; Kiyimba, Blaise (Student's Journal of Health Research Africa, 2023)
Introduction: The prevalence of organophosphate poisoning has been increasing over the years, with significant hospitalization following the introduction of various pesticides. The inception of different regulating agencies against organophosphate utilization has been effective in developed countries, unlike low- and middle-income countries. Continuous monitoring of vulnerable populations, such as children, and depressed and anxious individuals, is necessary for reducing poisoning cases. Case: We discussed a 2-year and 6-month-old male child who was previously healthy and was brought into our pediatric emergency unit of a general hospital with a history of ingestion of fluid that he thought was milk. We present the sequelae of events from the ingestion of the substance until discharge from the facility. Additionally, we elaborate on the different preparations for managing any toddler with organophosphate poisoning. Conclusion: Appropriate use of these compounds, instruction of the public about their harmful effects, and restriction of their uncontrolled sales by legal regulations can reduce the incidence of organophosphate poisoning. Promoting emergency management strategies among parents concerning the management of acute poisoning is vital in promoting better children’s outcomes. Recommendation: Heath regulation bodies must take an interest in educating health workers and the community concerning organophosphate poisoning and its management, especially in a limited resource setting.